Hubungan Paparan Asap Rokok, Asupan Gizi Ibu, dan Riwayat Kadar Hb dengan Kejadian BBLR di Wilayah Kerja Puskesmas Cinangka Serang Banten Tahun 2023 - Ika Siti Nurjannah (Elisabeth Health Jurnal, 2023)
Introduction: Babies with Low Birth Weight (LBW), which is less than 2,500 grams, is a health problem that contributes to infant mortality. One of the causes is from the mother, fetus, and the environment. This study aims to determine the relationship between exposure to cigarette smoke, maternal nutritional intake, and history of HB levels with the incidence of LBW.Methods: Respondents in this study are 49 respondents in Working Area of Cinangka Health Centre, Serang, Banten with probability sampling tenchnique. This research is quantitative research with analytical descriptive technique with a cross sectional approach.Results: The results of this study indicate that there is a significant relationship between exposure to cigarette smoke, the Odds Ratio (OR) is 4.500 (1.206-16.785) with 95%, the Odds Ratio (OR) maternal nutrition intake is 0.209 (0.054-0.808) with 95%, and the Odds Ratio (OR) history of Hb Levels with LBW Incident is 0.222 (0.060-0.829) with 95% which is protective factors.Conclusion: The conclusion of this study is that there is a relationship between exposure to cigarette smoke, maternal nutritional intake, and a history of HB levels with the incidence of LBW in the Cinangka Health Center Work Area.